2017
DOI: 10.1111/dme.13532
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 diabetes remission 2 years post Roux‐en‐Y gastric bypass and sleeve gastrectomy: the role of the weight loss and comparison of DiaRem and DiaBetter scores

Abstract: AimsThe comparative efficacy of Roux‐en‐Y gastric bypass (RYGB) and sleeve gastrectomy on Type 2 diabetes remission and the role of weight loss are unclear. The DiaRem diabetes remission prediction score uses HbA1c, age and diabetes medications but not diabetes duration. The aim of this study was to compare the DiaRem with the DiaBetter score that includes diabetes duration, upon combined (complete plus partial) 2‐year post‐surgery diabetes remission in people following RYGB and sleeve gastrectomy, and to inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(60 citation statements)
references
References 27 publications
2
56
0
2
Order By: Relevance
“…Differences of such magnitude are also clinically significant, as a previous study reports a 7% increase in the odds of type 2 diabetes remission for every 1% weight loss [36]. This finding is in partial agreement with a prospective study which reported a borderline positive association between number of confidants and %EWL [22].…”
Section: Resultssupporting
confidence: 83%
“…Differences of such magnitude are also clinically significant, as a previous study reports a 7% increase in the odds of type 2 diabetes remission for every 1% weight loss [36]. This finding is in partial agreement with a prospective study which reported a borderline positive association between number of confidants and %EWL [22].…”
Section: Resultssupporting
confidence: 83%
“…To determine the effect of fasting insulin and glucose reduction, the degree of %EWL was more significant than the type of surgery. This may be the reason why LRYGB was more effective than LSG as T2DM treatment [16].…”
Section: T2dmmentioning
confidence: 99%
“…Moreover, conclusions of studies that compared LRYGB with LSG in the remission of complications remained controversial. Some studies indicated that LRYGB was superior to LSG [5,15,16] in the remission of T2DM, while other studies suggested that the remission rates were similar in both groups [17]. Previous studies had shown an advantage for LRYGB in the remission of hypertension [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Since DR following BS is not universal, there has been progress in developing scoring systems (DiaRem 56 , ABCD score 57 , Ad-DiaRem 58 and DiaBetter 59 ) to predict patients' likelihood to achieve DR one year following surgery. These scores use several routine clinical parameters demonstrated to be involved with DR or non-DR.…”
Section: Bariatric Surgery and Type 2 Diabetes Improvementmentioning
confidence: 99%